Collision-Conscious Multi-Pass Flank Milling of Complicated Parts Based on Stripification. (April 2023) - He, Dong; Li, Zhaoyu; Li, Xiangyu; Li, Yamin; Tang, Kai
Abstract: Flank milling of a surface means to use the linear side of a tool to machine the surface while subject to all the necessary constraints such as collision-free and maximum cusp height. For a general freeform surface, it is always necessary to require multiple passes of a tool path to machine the surface. Because of the much-enlarged material removal rate by flank milling, at least at the semi-finish stage, it is preferred over the conventional machining type of point-milling, especially for those heavy and large industrial parts such as centrifugal impellers and turbine blades. Unfortunately, due to the much-worsened tool-surface collision condition in flank milling, for a complex part surface, it is extremely difficult to determine a correct collision-free multi-pass flank milling tool path while satisfying the maximum cusp height requirement. In this paper, we present an algorithm for this problem. The crux of our method is the establishment of a collision-conscious vector field on an offset surface of the part surface, which encapsulates degrees of both local gouging and global accessibility. This offset mesh is further segmented such that each patch will have only a curl-free vector field. The level-set method is then utilized to fit a scalar field on each patch whose iso-curves naturally form a set of initial tool cutter contact rulings, which are further optimized and propagated to constitute a stripification of the patch comprising a set of quad strips, while respecting the constraints of no-overcut, collision-free, and maximum cusp height. Finally, for each patch, a multi-pass flank milling tool path is generated based on the rulings of the optimized quad strips. Both computer simulation and physical cutting experiments have been carried out, and the experimental results give a positive confirmation on the correctness and effectiveness of the proposed method. Highlights: A new multi-pass flank milling method for complicated surface mesh is proposed. A collision-conscious vector field considers tool path accessibility and smoothness. The field helps to partition the part and each partition is covered by quad strips. The tool paths are generated on the strips tending to the machining constraints. Simulations and experiments have verified the effectiveness of our method.